2016
DOI: 10.1016/j.lingua.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Refining intervention: The acquisition of featural relations in object A-bar dependencies

Abstract: Refining intervention: The acquisition of featural relations in object A-bar dependencies The presence of a [+NP] feature (representing a 'lexical restriction') on both the moved DP and the intervening subject is assumed to hinder children's comprehension of object A-bar dependencies (Friedmann et al. 2009). In order to better understand the nature and impact of this feature and its interaction with animacy, we assessed comprehension of object relative clauses and wh-questions in French-speaking children aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 42 publications
6
35
0
4
Order By: Relevance
“…Although animacy is not part of the feature set of the clausal inflectional head, this feature has been argued to be relevant for movement (see Bianchi, 2006), which may then be the crucial ingredient for a feature to enter into the computation of locality, rather than a feature being part of the featural composition of the clausal inflectional head. For more on this perspective, see Bentea, Durrleman, and Rizzi (2016).…”
Section: Notesmentioning
confidence: 99%
“…Although animacy is not part of the feature set of the clausal inflectional head, this feature has been argued to be relevant for movement (see Bianchi, 2006), which may then be the crucial ingredient for a feature to enter into the computation of locality, rather than a feature being part of the featural composition of the clausal inflectional head. For more on this perspective, see Bentea, Durrleman, and Rizzi (2016).…”
Section: Notesmentioning
confidence: 99%
“…This possibility could be tested in future studies by performing experimental manipulations currently examined in the A‐bar dependency field, e.g. by using inanimate interveners, which appear to be less disruptive than animate ones (Bentea and Durrleman ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the discourse properties of object questions have received little attention in the literature on intervention. However, recent studies have found that these questions also exhibit strong intervention effects, particularly in language-impaired individuals (Garraffa & Grillo 2008;Friedmann & Novogrodsky 2011;Bentea et al 2016). As the discourse function of object questions differs markedly to that of object relatives, they provide a rigorous test of the generalisability of the discourse account.…”
Section: Introductionmentioning
confidence: 99%